Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Proceedings of the 29th Annual Computer Security Applications Conference 2013
DOI: 10.1145/2523649.2523665
|View full text |Cite
|
Sign up to set email alerts
|

No attack necessary

Abstract: Much of the Internet's end-to-end security relies on the SSL/TLS protocol along with its underlying X.509 certificate infrastructure. However, the system remains quite brittle due to its liberal delegation of signing authority: a single compromised certification authority undermines trust globally. Several recent high-profile incidents have demonstrated this shortcoming convincingly. Over time, the security community has proposed a number of counter measures to increase the security of the certificate ecosyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Given that trust anchors can issue intermediate CA certificates (and intermediates can be enabled to do the same), a site certificate is browser-acceptable if the browser can build a chain of certificates that lead to a trust anchor. One study found 20% of valid certificates required no intermediate and 38% used one [18].…”
Section: Transitivity Of Trustmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that trust anchors can issue intermediate CA certificates (and intermediates can be enabled to do the same), a site certificate is browser-acceptable if the browser can build a chain of certificates that lead to a trust anchor. One study found 20% of valid certificates required no intermediate and 38% used one [18].…”
Section: Transitivity Of Trustmentioning
confidence: 99%
“…Thus, current browsers fail open, accepting certificates for which revocation information cannot be located (browsers should downgrade all EV certificates to a regular certificate, or warn, as responsive revocation is an EV requirement). 18 In response to the failings of revocation, some browsers (e.g., Chrome) maintain an updatable certificate blacklist (see Section V-C).…”
Section: Maintenance Of Trustmentioning
confidence: 99%
See 2 more Smart Citations